(untitled) (Journal of the College of Basic Education, 2022)
This investigation has been conducted to study water quality of the Tigris and the Euphrates River with the progress of time. The BOD values increasing with time increase from 1970 to 2010. The increasing was in Euphrates water more than Tigris water .Also, The EC values have been increased .